YARGITAY KARARLARI ÇERÇEVESİNDE MARKA HÜKÜMSÜZLÜK DAVALARINDA ZARAR GÖREN KİŞİLER - (:unkn) unknown (My University, 2015)
556 Sayılı KHK'nın 43. Maddesinde yer alan hü- kümsüzlük davalarında davacı sıfatı açısından "Zarar Gören Kişiler" ibaresi mehaz 40/94 Sayılı TÜZÜK hükümlerine uyumlu değildir. Bu uyumsuzluğun halihazırda mevcut Markalar Kanunu Tasarısı Tasla- ğı'nda aynen devam ettiği görülmektedir. "Zarar Gören Kişiler" ibaresinin Türk Hukuk Doktrininde geniş olarak yorumlanması gerektiği hakim bir şekilde belirtilse bile bazı Yargıtay kararlarında farklı yorumlanması da söz konusu olabilmektedir. Bu nedenle öncelikle uygulama açısından çok önemli olan bu hükmün mehaza uygun hale getirilmesi (Hü- kümsüzlük ve iptal sebepleri dikkate alınarak) davacı sıfatının belirlenmesi gerekmektedir. Ancak bu yapılmadığı ve mevcut düzenlemenin aynen devam etmesi halinde ise HMKm.114 vd'da yer alan "hukuki yarar" kavramı dikkate alınarak hükümsüzlük davası aç- manın herkese tanınmasını gerektirecek kadar geniş yorumlanmasının isabetli olacaktır.

Te use of the term “Injured Person”, in Article 43 of Law Decree No: 556 to identify those that are entitled to bring an action for invalidity, is not compatible with the relevant provisions of EU Regulation No: 40/94, by which the Decree Law is inspired. Tis incompatibility seems to be retained in the current version of the Draf Law on Trademarks. Even though the prevailing opinion of Turkish law doctrine argues that the term “Injured Person” must be interpreted broadly, this term is also interpreted diferently in some decisions of the Court of Cassation (Yargıtay). Terefore, the aforementioned provision of Law Decree No: 556, which is of high importance for the practice, must first of all be revised to be compatible with Regulation No: 40/94, with regard to grounds for invalidity and revocation. However, in case the current version of the provision cannot be revised as suggested, then it should be interpreted broadly enough to entitle everyone to bring an action for invalidity, through taking into account the concept of “legal interest” laid down in Article 114 of Civil Procedural Law.
THE CONCEPT OF INJURED PERSONS IN TRADEMARK INVALIDATION ACTIONS IN THE LIGHT OF THE PRECEDENTS OF THE COURT OF CASSATION
Keywords: Hukuk